COMPETITIVE STRATEGY TO ACHIEVE ISO-9001 CERTIFICATION IN SMALL AND MEDIUM SUPPLY ENTERPRISES IN CIUDAD JUAREZ, CHIHUAHUA, MEXICO - Oscar Alejandro Rodarte Contreras; Francisco Arturo Bribiescas Silva (European Scientific Journal, ESJ, 2014)
Competitiveness is a predominant factor in today supply companies of the manufacturing industry. In this paper, the analysis shows that it took place in the region of Ciudad Juarez, Chihuahua, Mexico in SMEs. To that end, a search for competitive strategies proposed by different authors in the literature of the subject. Besides performing a critical analysis of quality requirements that the customer deems necessary in its suppliers through a questionnaire created through Kano model focused on customer satisfaction. As a result of research results in a business strategy focused on obtaining the certification in quality management systems in the ISO international standard for small and medium businesses in the city. Also the result of this work demonstrates the degree of importance of having a certification in quality management system in the selection of suppliers for manufacturing companies in the region.